Relações sociais de callithrix jacchus machos: competição ou cooperação? - Santiago, Alessandra Maressa Lessa (2012)
The group Callithrichidae is characterized by the flexibility in its mating system. This fact generates questions about the mechanisms that Callithrix jacchus males reach the breeding position in a group and how they prevent the subordinates reproduction, since the competition apparently happens with less intensity when compared to the females. Studies have shown the importance of social interactions and kinship among individuals in the distribution of mating opportunities in a group. This work aimed to evaluate if dyads of Callithrix jacchus males acted socially different due to kinship. We observed the agonistic and affiliative behaviours made by the males when associated in dyads (Phase 1) and when these dyads received a female (Phase 2), which was introduced in the pair`s cage for 45 minutes. In the phase 2, we also accounted for the sexual interactions between males and female in each trio. We used 16 males, 8 related (brothers-R) and 8 nonrelated (NR), as well as 8 females. Each phase lasted 4 weeks, with 3 observations/week, during 15 min/male in phase 1 and 2. In the first phase, two pairs of R males had a contested dominance and the other two, just like in the NR males, had an uncontested dominance. The NR dominant males were more aggressive than the subordinates. With the female`s entrance in the cage, all male pairs began to have an uncontested dominance. The NR males aggression frequency rose along with the subordinates` submission. In the R males, the frequency of grooming and physical contact was higher than in the NR males. So, we conclude that the low levels of agonism presented by the R males, along with the higher tolerance shown amongst them, lead us to believe that kinship attenuate the competition among these males